New insights into emotion valence and loyalty intentions in relational exchanges - McKechnie, Sally; Nath, Prithwiraj; Xun, Jiyao (Wiley, 2018)
This research examines how emotion valence and future intentions arising from relational exchanges with a service firm depend on a consumer's level of goal attainment and locus of causality (firm vs. self) of relational outcomes. Drawing on the theories of goal-directed behavior and agency of causation, this study hypothesizes that levels of goal attainment and locus of causality influence the generation of positive emotions (gratitude), negative emotions (grudge and guilt), relational mediators (trust and commitment), and subsequent future intentions to remain loyal to the firm. Based on a controlled experiment with 284 subjects in a consumer-determined relationship setting, the research finds that emotion valence and future loyalty intentions are contingent upon the fulfillment of relational objectives of individual consumers and the agency of causation for the outcome of the relational exchanges. In doing so, this study delineates the conditioning mechanism that directs how emotion valence influences behavioral intentions. The study contributes to the consumer behavior and services marketing literatures on consumption-based emotions and has significant practice implications for relational behaviors.